Diabetes is too important to be left to diabetologists alone - Sanjay Kalra; Suresh Sharma (Journal of the Pakistan Medical Association, 2022)
The Challenge is Great Diabetes is a pandemic which shows no signs of slowing down. Recent developments, such as the COVID 19 epidemic, have highlighted the role of diabetes specifically uncontrolled diabetes, in defining health outcomes.1 We have known, for long, the role of glycaemic control in improving long term vascular outcomes. Now, however, we have robust data which demonstrates that a 1% reduction in glycated haemoglobin can reduce probability of getting severe COVID19 by 21%.2 A major obstacle to ensuring euglycaemia is lack of education. Lack of awareness, at individual, family and societal level, leads to delayed recognition, diagnosis and management of diabetes.3 This is turn, creates a situation where control becomes progressively more difficult to achieve, and satisfaction with health care becomes lesser and lesser.